Doubly differentiated limit

Calculus Level 2

Let f : R R f:\mathbb{R} \rightarrow \mathbb{R} be such that f f'' is continuous on R \mathbb{R} and f ( 0 ) = 1 f(0)=1 , f ( 0 ) = 0 f'(0)=0 and f ( 0 ) = 1 f''(0)=-1 . Then find lim x ( f ( 2 x ) ) x \displaystyle \lim_{x \to \infty} {\Bigl(} f{\Bigl(} {\sqrt{\frac{2}{x}}}{\Bigl)} {\Bigl)} ^x correct to three decimal places.


The answer is 0.368.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chris Lewis
Dec 7, 2020

From the given derivatives at x = 0 x=0 , the Taylor series of f ( x ) f(x) is f ( x ) = 1 1 2 x 2 + f(x)=1-\frac12 x^2+\cdots

When x x is large, f ( 2 x ) 1 1 x f\left(\sqrt{\frac{2}{x}}\right) \approx 1-\frac{1}{x}

so the limit we want is lim x ( 1 1 x ) x = e 1 \lim_{x\to \infty} \left(1-\frac{1}{x}\right)^x=\boxed{e^{-1}}

Pi Han Goh
Dec 7, 2020

Chris Lewis gave the best possible solution. Here's my approach: Let L L denote the value of this limit, Since the limit is in the indeterminate form 1 1^\infty , I'm tempted to use L'Hôpital's rule (LH), ln L = lim x x ln ( f ( 2 x ) ) 0 = lim x ln ( f ( 2 x ) ) 1 / x , let y = 1 x 0 = lim y 0 + ln ( f ( 2 y ) ) y , this is a 0 0 case, apply LH 0 = lim y 0 + f ( 2 y ) 1 / ( 2 y ) f ( 2 y ) , let z = 2 y 0 = lim z 0 + f ( z ) 1 / z f ( z ) = lim z 0 + f ( z ) z f ( z ) , Another 0 0 case. Apply LH 0 = lim z 0 + f ( z ) z f ( z ) + f ( z ) = 1 1 + 0 = 1 \newcommand{\limxinfty}{\lim \limits_{x\to\infty} } \newcommand{\limyzero}{ \lim \limits_{y\to0^+} } \newcommand{\limzzero}{ \lim \limits_{z\to0^+} } \begin{array} {r c l l} \ln L &=& \limxinfty x \ln \left( f \left( \sqrt{\frac 2x} \right) \right) \\ \phantom0 \\ &=& \lim \limits_{x\to\infty} \dfrac{ \ln \left( f \left( \sqrt{\frac 2x} \right) \right) } { 1/x}, &\quad \text{let }y= \frac1x \\ \phantom0 \\ &=& \limyzero \dfrac{ \ln \left( f \left( \sqrt{2y} \right) \right) } { y} , & \quad \text{ this is a } \frac00 \text{ case, apply LH} \\ \phantom0 \\ &=& \limyzero \dfrac {f'(\sqrt{2y}) \cdot 1/(\sqrt {2y}) }{f(\sqrt{2y})}, \quad \text{ let }z= \sqrt{2y} \\ \phantom0 \\ &=& \limzzero \dfrac {f'(z) \cdot 1/z }{f(z)} = \lim \limits_{z\to0^+} \dfrac {f'(z) }{z \cdot f(z)}, & \quad \text{ Another } \frac00 \text{ case. Apply LH} \\ \phantom0 \\ &=& \limzzero \dfrac {f''(z) }{z \cdot f'(z) + f(z)} = \dfrac{-1}{1 + 0} = -1 \end{array} The answer is L = e 1 0.368 . L = e^{-1} \approx \boxed{0.368} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...